UJI AKTIVITAS ANTI RAYAP EKSTRAK RIMPANG LEMPUYANG GAJAH (ZINGIBER ZERUMBET SMITH) TERHADAP RAYAP TANAH (COPTOTERMES CURVIGNATHUS HOLMGREN) - Tafsir, Ahmad; Wardenaar, Evy; dina, Wah (Universitas Tanjungpura, 2015)
The study aims to find out the effect of different dosage pinecone ginger rhizome extract (Zingiber zerumbet Smith) against subterranean termite (Coptotermes curvignathus Holmgren) and determine the optimal dose as antitermite to C.curvignathus. Rhizome of Z.zerumbet was macerated with methanol for 24 hours. Then evaporated to get the extract, the extractive obtained was given Â to Â Whatman filter paper with a dose of 0ml, 0.1 ml, 0.2 ml, 0.3 ml, and 0.4 ml respectively. The filter paper then used in bioassay test to C.curvignathus. The result showed that the highest antitermite activity is 100% termite mortality and the lowest weight lost of filter paper 0.3392%, at 0.4 ml extractive dose the increase of extractive will made the higher of termite mortality and decrease of filter paper weight loss. Optimal dose of rhizome extract Z.zerumbet was 0.3 ml. Key words: Antitermite, (C. curvignathus), Extract, Ginger, (Z. zerumbet).